Point load strengths of Tertiary sedimentary rocks from the Batu Arang area, Peninsular Malaysia - Raj, J. K. (Malaysian Journal of Science, 1995)
Tertiary sedimentary rocks comprising silty to sandy shales interbedded with thin •structureless clay layers, fine to coarse grained sandstones and a number of lignite seams are found in the Batu Arang area. Field point load tests on silty to sandy shales from three stratigraphic levels with moisture contents of 18.9, 14.3 and 10.3 % yield strength indices of 0.15, 0.30 and 0.52 MPa. These indices reflect variations in moisture contents as air dried samples with a moisture content of 0.8 % from the different levels yield a strength index of 1.40 MPa. A similar variation with moisture content is shown by the thin clay interbeds which yield strength indices of 0.07 and 0.88 MPa at moisture contents of 14.9 and 1.9 0/0. Field point load tests on blocks of the lignite seams yield strength indices ranging from 0.24 to 1.60 MPa, the range reflecting a decrease of strength owing to the influence of inherent fractures with increasing sample size. Point load strengths of the Tertiary silty to sandy shales and clay interbeds are thus dependent upon moisture content, whereas those of the lignite seams are dependent upon sample size.